2020
DOI: 10.1016/j.jmig.2020.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Outcomes following Use of Barbed Suture during Laparoscopic Myomectomy

Abstract: To review pregnancy outcomes after laparoscopic myomectomy with the use of barbed suture. Design: Retrospective cohort study and follow-up survey. Setting: Single, large academic medical center. Patients: Patients who underwent laparoscopic myomectomy with the use of barbed suture for myometrial closure between 2008 and 2016. Intervention: Laparoscopic myomectomy and a follow-up survey regarding pregnancy outcome. Measurements and Main Results: A total of 486 patients met inclusion criteria and underwent a lap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…As the authors concluded, the available data regards patients with previous barbed suture, lacking information about fertility outcomes in control groups. Considering barbed suture outcomes, pregnancy rates of 71% have been reported ( 61 ), similar to other studies that evaluated laparoscopic myomectomy without differentiation ( 17 , 62 ). Cesarean sections were performed frequently, and the reported complications included preterm birth, abnormal placentation, hypertensive disorders, growth restriction, and myoma degeneration (18 of 110 pregnancies) ( 61 ).…”
Section: Impact Of Sutures Type On Fertility and Pregnancy Outcomessupporting
confidence: 81%
“…As the authors concluded, the available data regards patients with previous barbed suture, lacking information about fertility outcomes in control groups. Considering barbed suture outcomes, pregnancy rates of 71% have been reported ( 61 ), similar to other studies that evaluated laparoscopic myomectomy without differentiation ( 17 , 62 ). Cesarean sections were performed frequently, and the reported complications included preterm birth, abnormal placentation, hypertensive disorders, growth restriction, and myoma degeneration (18 of 110 pregnancies) ( 61 ).…”
Section: Impact Of Sutures Type On Fertility and Pregnancy Outcomessupporting
confidence: 81%
“…In regard to the effect of barbed sutures on fertility and pregnancy after myomectomy, a recent retrospective cohort study and follow-up survey by Pepin et al . 55 showed that pregnancy outcomes after laparoscopic myomectomy with barbed suture are comparable to the available literature on pregnancy outcomes with conventional smooth sutures, making the former safe to use in procedures that are indicated to improve fertility and obstetrical outcomes.…”
Section: Barbed Sutures In Laparoscopic Surgerymentioning
confidence: 74%
“…A retrospective cohort study reported no uterine ruptures in 110 pregnancies, following laparoscopic myomectomy using barbed sutures before pregnancy [ 9 ]. Perinatal outcomes in myomectomy during pregnancy using barbed sutures are unclear, as there are no other reported cases using the same sutures.…”
Section: Discussionmentioning
confidence: 99%